Pengembangan Pemasaran Batik Dalam Meningkatkan Penjualan Produk di UMKM Batik Art And Gallery Lochatara - Asrifah, Meila Nur; Prameswari, Rachmalia Eka; Anisa, Choiri Nur; Rismawati, Putri; Anggraini, Nimas Ayu; Mawwadah, Wildati (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The MSME sector plays an important role in the economic development of society. In addition to playing a strategic role in development, MSMEs also have a function as a means to distribute the results of existing development. The existence of MSMEs in Indonesia is growing rapidly and mushrooming everywhere. MSMEs have a big role in both domestic regional and national strategies. Marketing is the core activity of running a business, so it must be done carefully. Marketing activities are the foundation for running a business. Marketing is a series of activities in a trading business that aim to meet actual and potential consumer demand for the goods or services offered. In carrying out the marketing of MSMEs, Batik and Art Lochatara have not been optimal in the use of social media and are still lacking in overall implementation. So that this service aims to increase Natural Resources, Human resources, and Capital Resources. With this community service, a number of employees and the public who are members of the Batik and Art Lochatara community have sufficiently increased their knowledge about the use of social media as a means of introducing MSME products and distributing brochures that are effectively used for marketing in tourist areas.